Modeling Communication Between the Public and the Authorities while Implementing Innovative Projects in the Context of E-Democracy and Public Administration - Shyian, A.A.; Azarova, A.A.; Nіkіfоrоvа, L.O.; Tkachuk, L.M.; Azarova, V.V. (Наука та інновації, 2020)
Introduction. E-democracy and e-government become an increasingly common attribute of people's lives, since they give is an opportunity to attract population masses to the discussion of both economic and social, as well as managerial innovations. The society urgently requires innovation in the organization of public and regional administration. Problem Statement. Adjemoglu and Robinson have shown that the necessary factor for the success of public or region development is the presence of inclusive political and economic institutions. Inclusive institutions involve the widest possible population in decision-making. Moreover, namely the political institutions (which are crucial for involving as much as possible the public to making decision) determine successful development of society. Innovative projects are the driver of economic development, so the involvement of the general public in their discussion, decision-making, implementation and analysis of the results is an extremely important factor. Many authors have emphasized that the digitalization of information is an important factor for the formation and development of a developed society. Purpose. The purpose of this research is to develop approaches to modeling the communication channels of the public and authorities under the conditions of innovation project implementing in the context of e-democracy and public administration. Materials and Methods. The research uses the methods of system analysis, game theory, structural, functional, and logical analysis. Results. Innovative projects are supported primarily by the middle class, as evidenced by the Hotelling model (the median voter model). The analysis of existing in Ukraine functional model of communication between the public and the authorities while implementing innovation projects has revealed a number of its shortcomings. To correct them, a scheme for optimizing the communication between the authorities and the public by means of e-democracy while implementing an innovation project has been proposed. The necessity of attracting media, experts, and analysts at each stage of the implementation of the innovation project has been justified. Conclusions. The described communication channel includes electronic media and the community of experts and analysts as compulsory components. It enables the creation an effective system of feedbacks between the authorities and the public which allows making optimal decisions and monitoring the socio-economic development of society.